Aspek Biologis Pergerakan Gigi secara Ortodonsi - Muhammad Nurul Amin; Nur Permatasari (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2016)
Orthodontic appliance used to correct malocclusion which may include dental abnormalities, jaw relationship abnormalities, growth disorder of bone-forming facial or oral soft tissues disorder. Mechanical force of orthodontic appliance applied to suppress the teeth and periodontal tissue including gingiva, periodontal ligament and alveolar bone. This process involves the alveolar bone remodeling. Orthodontic mechanical force will cause the periodontal area is divided into two areas: pressure and strain area. In the pressure area, mechanical force will stimulate osteoclasts to perform alveolar bone resorption. Whereas strain area, osteoblasts will perform new alveolar bone formation. Orthodontic tooth movement has three phases process. The phase is initial phase, lag phase and postlag phase. The third phase of tooth movement mechanism involving cellular and molecular reactions in the periodontal tissues.